Team Games Tournament Assisted by Math Journal as An Effort to Improve Students’ Numeracy Skills - Amin, Hafidhoh Lailiatil Ummah; Zuhriawan, M. Qoyum; Nasrulloh, Muhammad Farid; Umardiyah, Fitri (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The research aims to improve students' numeracy skills by applying Team Games Tournament (TGT) type cooperative learning assisted by Math Journal. This research used a quantitative approach with a pre-experimental design method of one group pretest-posttest type. The research subjects were students of Grade VIII of SMP Negeri 2 Perak Jombang. The research has used instruments in the form of questions that consist of pre-test and post-test, questionnaires as supporting data and TGT teaching modules. The test instrument was supported by the results of a student questionnaire. The data analysis technique used is hypothesis testing using paired samples t-test. Based on the results of the paired sample t-test, the significance value is 0.000. The significance value obtained is 0.000 <0.05 error level. So it can be concluded that Ho is rejected, which means that there is an effect of the application of TGT assisted by Math Journal on students' numeracy skills. Therefore, it can be concluded that the numeracy skills of VIII grade students of SMP Negeri 2 Perak increased after the application of TGT assisted by Math Journal.